O juiz das garantias no processo penal brasileiro à luz do sistema acusatório (de acordo com o PL 156/09, do Senado Federal) - Schneider, Gabriela (Universidade do Vale do Rio dos Sinos, 2011)
This paper presents the debate concerning the creation of the Guarantee Judge in light of the accusatory system, according to the law project 156/09 of the Brazilian Federal Senate - which aims to reform the Brazilian Code of Criminal Procedure (CCP) -, being this judge a special prosecutor to act in the preliminary stage of criminal investigation. The research will approach, at first, the preliminary investigation systems (police, investigating judge and investigating prosecutor), the foundations of the existence of an investigation, and the main methods of the investigation in Brazil. In a second phase, the work will focus on the criminal procedure systems (inquisitorial, accusatory and mixed), the principles of impartiality and neutrality, as well as the concept of Guarantee Judge, showing that this institute has already been adopted in Portugal and in the province of Buenos Aires, each one with its own peculiar structure of criminal procedure. The research will highlight, finally, the analysis of the Guarantee Judge within our procedural law, according to the draft of the CCP reform. The main points and arguments regarding the implementation of this institute in Brazil will be emphasized – as, for example, what will be the main responsibilities of this judge and what are the inconsistencies of the law in the context of the accusatory system. Furthermore, it will be presented a comparative table between Brazil, Portugal and the province of Buenos Aires - which highlights their similarities and differences regarding to the approached topics.
Keywords: Processo penal; Juiz das garantias; Investigação preliminar; Sistema acusatório; Imparcialidade; Criminal procedure; Guarantee judge; Preliminary investigation; Accusatory system; Impartiality